Extending use of instructional exchanges to research on teacher education - Chazan, Daniel; Herbst, Patricio (Frontiers in Education, 2023)
This article extends use of the construct of instructional exchanges from analysis of mathematics instruction to analysis of mathematics teacher education. We describe four ways in which teacher candidates exchange their work for teacher educators’ assessments of their learning of mathematics teaching and illustrate how such exchanges are a subset of a more general kind of activity, transaction of practice. The examination of teacher education closes by looking back at what the extension of use of instruction exchanges to teacher education and attention to transaction of practice more generally might suggest as ways to develop a greater range of tasks for use in mathematics teaching in compulsory settings that would allow mathematics teachers in compulsory settings to make a wider variety of claims about what it is that their students have learned. The article also works across these two instructional contexts by highlighting ways in which student work formats and technological tools can support instructional exchanges in the mathematics and in the teacher education classroom.